Effect of the rotifer brachionus plicatilis and brine shrimp Artemia naulii as food on the survival and metamorphosis of Scylla olivacea laevae. - Dalmacio, Karen Hope A.
A feeding experiment was conducted to determine which type of food organisms will be preferred by the Scylla olivacea larvae., Three treatments were used in this study of Scylla olivacea larvae. In treatment I, Brachionus plicatilis was given at 10 ind/ml. In treatment II, a combination of Brachionus plicatilis (10 ind/ml) and newly-hatched Artemia nauplii (1-5 ind/ml given at increasing concentration with increasing zoeal stage). Artemia nauplii alone was given at 1-5 ind/ml in treatment III. Every treatment was replicated three times. Experiments was conducted in a 3.8-L plastic container filled with 3L of seawater at a salinity range of 30-32ppt and temperature range of 26-30 degrees centigrade. The stocking density of larvae was 10 larvae/L. There was no aeration provided. There was complete transfer of the larvae to a new container with the desired foor organism. Daily survival and metamorphosis were monitored. Results of the experiment show that Brachionus-fed larvae gave the highest survival from Z1-Z4. However, there is prolonged molting of Z3 larvae to Z4. Larvae in this treatment had lower metamorphosis from Z5 to megalopa. On the other hand, larvae fed with Artemia alone had a drastic drop in survival from 93.3% in day to 42.2% day 2, although larvae that survived reached megalopa. larvae with Artemia in their diet (treatments 2 & 3) had good metamorphosis. Larvae fed with combination diet had good survival but those larvae fed with the combination diet supported highest survival and growth up to megalopa.